Quality enhancement in production of safety pins through the implementation of Kaizen activity - AbdulAziz Alneaimi, Hozaifah (2018)
Kaizen Activities (KA) is one of Lean Manufacturing tools usually being used to eliminate or reduce waste in manufacturing industries. KA is a continuous improvement method which is dedicated to the improvement of productivity, efficiency, quality and, in general, of business excellence. This study was conducted to improve quality in a metal manufacturing company by implementing KA. The company produces sewing notions, garments and craft accessories such as safety pins, pearliest pins, ball pins, straight pins, sew-on press fasteners and many more. The main source of waste in the company is 70% rejected loads of safety pins per day due to some quality issues. Therefore, the main targets of this project are to identify the quality issues occurring in the production of safety pins, analyzing it using analysis methods, and implement KA to improve quality and reduce rejection rates. The methodology starts with dividing the manufacturing company into two departments which are pretreatment and posttreatment. KA is implemented in each department by which the existing problem is identified and analyzed. Once the causes of the problems are identified, solutions were generated followed by quality check tests to indicate any improvement. This study shows that the rejection in safety pin production was due to the rough point issue which is uneven surface on the tip of the safety pin. The root causes for this problem were dust on the wire of the safety pins and the inaccurately supplied voltage and current of the nickel plating tanks. The implementation of KA in this company has improved the production quality of the safety pins and reduce rejection from 70% to 40 % in less than a year. KA in the company is still ongoing as it is continuous improvement strategy to reach zero defects with the best quality result.